Հակոբ քահանա Կեսարացու «Հիշատակարանն» իբրև աղբյուր - Մուրադյան, Սամվել («Զանգակ - 97»)
The Synodicon by priest Hacob the Caesarian is the depiction of the life and activities of one of the mosl prominent figures of the first half of XV Century, Grigor Lhe Caesarian, who was a clergyman, a teacher, a negotiator and a public figure. At the same time, the Synodicon by priest Hacob the Caesarian provides interesting data on the history of manuscript collections existing in Constantinopolis and Caesaria. Similarly important are the evidences provided of literary works in translaüon. Thcrefore, the scientific publication of the original version of the Synodicon will enrich Armenology and Oriental studies with a reliable source.
Keywords: Հայոց պատմություն; Հայ գրականություն